SOSIALISASI KEKAYAAN INTELEKTUAL GUNA MENUMBUHKEMBANGKAN USAHA DALAM RANGKA MENGHADAPI PERSAINGAN GLOBAL PADA REVOLUSI 4.0 - Yanto, Oksidelfa; Susanto, Susanto; Nugroho, Agung; Santoso, Bambang; Gueci, Rizal S (Abdi Laksana : Jurnal Pengabdian Kepada Masyarakat, 2020)
The purpose of the implementation of Community Service entitled "The Socialization of Intellectual Property to Grow Businesses in the Context of Facing Global Competition in the Revolution 4.0" is as an effort to fulfill the obligations of the Higher Education Tri Dharma namely Community Service to be carried out at Bandung Lembang Floating Market on 19 October 2019 up to October 21, 2019. Based on the above, community service activities by providing information and or additional knowledge regarding Intellectual Property Rights. The method used in Community Service is in the form of counseling on the understanding of IPR and the importance of IPR for the business world. The types of IPR are also explained in detail. The Community Service Results obtained are the understanding and desire of PKM objects to administer and register IPR in the interests of their business.